Augmentation of Acquired Defect of the Forehead with Subperiosteal Silicone Implant - Krishnan, Rijesh; Chetty, Ramesh; Prakash, Ram (Journal of Orofacial Research, 2013)
normal, i.e. to look exceptional is also possible now due to availability of various surgical and nonsurgical methods available to common people to either remove signs of old age or toenhance the present appearance. The technology for these procedures like nose lifts, chin augmentation, wrinkle removal, breast enhancements, etc. has advanced in leaps and bounds. The positive side of such technology is its use in case of disfigurement due to trauma. When a person experiences trauma, the appearance may be compromised. But corrections of such disfigurement have become routine surgical practice. The use of hard and soft alloplastic materials is also very much the norm. The following case presentation is about a patient with a concave defect on his forehead. This concave defect was augmented with a preshaped silicone implant. This silicone was preshaped with reference to a contoured acrylic mold that was made on a facial moulage of the patient. As it was contoured on the moulage, it represented the exact need of the patient and hence the surgery was done just to place it subperiosteally. The result was a patient with minimal pain and less morbidity.